DETECTION OF ATHEROSCLEROSIS BY ANKLE BRACHIAL INDEX: EVALUATION OF PALPATORY METHOD VERSUS ULTRASOUND DOPPLER TECHNIQUE - Akhtar, Bilquis; Siddique, Saulat; Khan, Rafiq Ahmad; Zulfiqar, Sibgha (Journal of Ayub Medical College Abbottabad, 2009)
Background: Peripheral Arterial Disease [PAD], a manifestation of systemic atherosclerosis, is highly prevalent both in community studies and in primary care practice. Estimation of ankle brachial index [ABI] by ultrasound Doppler is the standard screening method for the detection of atherosclerosis in PAD patients. A low ABI is associated with increased risk of stroke or transient ischemic attack, ischemic heart disease and lower extremity gangrene. Though prevalence is high, physician and patient awareness of the condition is low. Primary care physicians are not well versed with the use of Doppler. Initial cost of the equipment is another adverse factor in low income countries. Detection of ankle systolic pressure by palpatory method may offer a cheap, simple and useful alternative approach in office care settings for early detection of disease. This may lead to the use of risk reduction strategies to avoid significant future morbidity and mortality. Methods: The sample size of 230 participants was identified. Patients were divided into control (100 cases), high risk asymptomatic (100 cases) and symptomatic groups (30 cases). Ankle systolic pressure was measured by digital palpation of foot arteries and by the gold standard Doppler technique in all patients in the three groups. PAD was defined by an ABI of <0.9. Results: In control group, mean±SD value of ABI was 1.0115±0.08167 by Doppler method versus 0.9923±0.08609 by palpatory method (p=0.1), in high risk asymptomatic group, 0.9838±0.08878 versus 0.9608±0.10377 (p=0.13) and in symptomatic group, 0.9302±0.14064 versus 0.9088±0.13274 (p=0.12). Against the more precise Doppler method, palpatory method was equally good in detecting the PAD positive cases. Conclusion: Early diagnosis of PAD in primary care practice by manual palpation of foot arteries is a reliable method to identify the population at risk and may lead to aggressive preventive therapies. Keywords: Peripheral arterial disease, cardiovascular disease, risk factors, ankle blood pressure, ankle brachial index.